2016
DOI: 10.4103/1008-682x.166433
|View full text |Cite
|
Sign up to set email alerts
|

Air quality control in the ART laboratory is a major determinant of IVF success

Abstract: A recently published article described how a fertility center in the United States implemented air quality control to newly designed in vitro fertilization (IVF) laboratory.1 A highly-efficient air filtration was achieved by installing a centered system supplying filtered air to the IVF laboratory and related critical areas, combining air particulate and volatile organic compound (VOC) filtration. As a consequence, live birth rates were increased by improvements in air quality. This article highlights the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Ideally, a risk management analysis concerning laboratory air quality should take into consideration not only to reduce but also to avoid the risks associated with poor air quality conditions. 50 Fair evidence indicates that laboratory air quality is associated with IVF outcome, although the evidence is not unequivocal. 46 , 47 , 51 Solid evidence based on prospective trials on the optimal solution for AQ in ART is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a risk management analysis concerning laboratory air quality should take into consideration not only to reduce but also to avoid the risks associated with poor air quality conditions. 50 Fair evidence indicates that laboratory air quality is associated with IVF outcome, although the evidence is not unequivocal. 46 , 47 , 51 Solid evidence based on prospective trials on the optimal solution for AQ in ART is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of air particulate filtration system on embryo development is debatable. While Heitmann and his colleagues [5] and Morbeck et al 2015 observed higher embryo development after improving air quality on the other hand, according to Esteves et al [33,34], little is known about the benefits of particulate filtration system [35][36][37]. Other important issues like indoor air quality, equipment/ furniture, construction and disposable materials, cleaning agents used, and personnel are less explored areas.…”
Section: Daymentioning
confidence: 99%
“…Throughout these processes, temperature and pH of working solutions should be kept constant, and state-of-the-art laboratory practices, including sterile techniques and control of air quality conditions, are important to ensure efficiency and safety [102,110]. In our center, sperm retrieval and micromanipulation of testicular sperm, which includes tissue processing, sperm injection, embryo culture, embryo transfer, and cryopreservation, are carried out in controlled environments [111][112][113].…”
Section: Role Of Ivf Laboratorymentioning
confidence: 99%